A local mesh refinement approach for large‐eddy simulations of turbulent flows. (5th February 2016) - Cevheri, M.; McSherry, R.; Stoesser, T.
Summary: In this paper, a local mesh refinement (LMR) scheme on Cartesian grids for large‐eddy simulations is presented. The approach improves the calculation of ghost cell pressures and velocities and combines LMR with high‐order interpolation schemes at the LMR interface and throughout the rest of the computational domain to ensure smooth and accurate transition of variables between grids of different resolution. The approach is validated for turbulent channel flow and flow over a matrix of wall‐mounted cubes for which reliable numerical and experimental data are available. Comparisons of predicted first‐order and second‐order turbulence statistics with the validation data demonstrated a convincing agreement. Importantly, it is shown that mean streamwise velocities and fluctuating turbulence quantities transition smoothly across coarse‐to‐fine and fine‐to‐coarse interfaces. © 2016 The Authors International Journal for Numerical Methods in Fluids Published by John Wiley & Sons Ltd Abstract : This paper introduces and validates a local mesh refinement approach for simulations of turbulent flows in complex domains. The method features high‐order interpolation schemes at the fine‐coarse mesh interfaces and uses up to fourth‐order central differencing schemes for convective and diffusive fluxes. It is shown that the local mesh refinement method is able to predict accurately first‐order and second‐order statistics of two challenging flows, a turbulent channel flow and the flow over a matrix of cubes. The method offers significant savings of computational resources due to the placement of very fine meshes into critical areas, for instance around the cubes, while for the rest of the domain, coarser meshes are employed.